Esterificação de ácido oléico sobre catalisadores mesoporosos tipo SO4-2/MCM-41 visando a produção de biodiesel - Nascimento, Alexsandra Rodrigues do (2009)
Climatic changes, largely induced by the use of fossil fuels and the concern with the sustainable development, has become renewable sources of energy extremely important. Nowadays, renewable sources of energy can be obtained, among several available processes, starting from transesterification, esterification and pyrolysis reaction. The esterification reaction can be carried out with homogeneous and heterogeneous catalysts, being them acids or basic. The use of heterogeneous acid catalysis it is preferable when intend to reduce significantly thr number separation and purifications stages the products, as well as, the possibility of reuse of the catalyst. In this context, researches have been developed using heterogeneous catalysts with the aim to study the biofuels obtaining. The aim os this work was to develop sulphated mesoporosos catalysts and it application in the biofuels production. The sample of MCM-41 was synthesized by the hydrothermal method, and it sample was submeted to sulphatation aiming obtain acid catalysts with different sulfphate concentrations. The catalysts were characterized by X-ray diffraction and infrared spectrocopy. The catalytic activity of the materials was evaluated in a batch reactor through the model reaction of oleic acid esterification. Through the X-ray diffaction results was observed that MCM-41 was obtained with success, because it presented the characteristic picks of the mesopouros structure mesoporosa. Infrared spectroscipy showed that calcination method carried out sucefuly with the elimination of the organic template, and, they were observed the main vibrational bands regarding the sulphate linked on the MCM-41 structure. The results obtained from the catalytic activity, in the esterification reactions were promising, because all the catalysts samples presented catalytic activity for the reaction at several temperatures. Levels of conversion of the sulphated MCM-41 were observed near to the of the reference catalysts, the sulphated zirconia and niobia.